Carbon sequestration potential of Alnus nepalensis at different land use systems and elevations of Gyalshing Forest Division, Sikkim, Eastern Himalaya, India - Ningwa Hangma Limboo; Sarswati Prakash Sati; Bhupendra Singh; Deepa Rawat; Manoj Kumar Riyal; Vinod Prasad Khanduri (Trees, Forests and People, 2025)
Estimation of vegetation composition, biomass, and soil properties along an elevational gradient is important to understand the variation in forest composition, biomass production, and physicochemical properties of the soil. In the present study, two land use systems were selected, i.e., Alnus nepalensis forests and A. nepalensis-based Silvi-horticulture systems in different elevations of Tashiding Range under Gyalshing Forest Division, Sikkim, to estimate the variation in vegetation structure, carbon storage potential, and soil characteristics. Four sites for each land use systems have been chosen at different elevations. Ten sample plots 10 × 10 m in size were laid out in each elevation. Physico-chemical properties of soil were analyzed at two different soil depths, i.e., 0–15 cm and 16–30 cm. The maximum tree density (540 trees per ha) and total basal area (19.72 m2 ha−1) were reported in A. nepalensis forests, while the tree density and tree basal area in A. nepalensis-based Silvi-horticulture system were recorded 430 trees per ha and 17.51 m2 ha-1, respectively. A. nepalensis forests stored a greater amount of tree carbon (150.74 C Mg ha−1) as compared to the A. nepalensis-based Silvi-horticulture system (93.68 C Mg ha−1). Soil pH and CEC were higher in A. nepalensis forests as compared to the A. nepalensis-based Silvi-horticulture system, while SOC, SOM, available N, available P, and available K were higher in the A. nepalensis-based Silvi-horticulture system. The study inferred that the forests with nitrogen-fixing species like Alnus increase the capability to sequester carbon and improve soil quality.